Challenges and Strategies in the Implementation of State Administrative Law in Village Governance in the Era of Village Autonomy (PT. LARPA JAYA PUBLISHER, 2025)
The implementation of administrative law in village governance during the era of village autonomy faces various complex challenges. This study aims to analyze the obstacles encountered by village officials and formulate effective strategies to enhance accountability, transparency, and professionalism in village administration. The research employs a literature review approach, analyzing eight scholarly articles published between 2012 and 2023 that discuss topics such as administrative capacity, regulation, supervision, community participation, and the use of information technology. The analysis reveals that the main challenges include limited administrative knowledge among village officials, overlapping national and local regulations, local political influence, and inadequate external supervision. Identified strategies include capacity building through training, strengthening community participation as a form of social control, regulatory harmonization, and the use of information technology to improve transparency and accountability. Implementing these strategies enables village governments to operate more professionally and respond effectively to community needs. This study provides both theoretical and practical contributions to village policy development, the strengthening of administrative law principles, and the improvement of local governance quality in Indonesia.